2019
DOI: 10.1002/cbf.3439
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine prevents desflurane‐induced motor neuron death through NF‐KappaB pathway

Abstract: Desflurane is one of the commonly used general anaesthetics. Recently, it was reported that desflurane caused neurotoxicity, raising concerns in clinical use. In this study, we found desflurane could affect viability and maturation in motor neurons.Dexmedetomidine, a α2-adrenergic receptor agonist, could attenuate the effect of desflurane on motor neurons. This process was mediated by NF-KappaB signalling.Interestingly, we also found that dexmedetomidine could recover the lesion in motor function and memory im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Interestingly, Des was found to have neurotoxic effects on motor neurons, and more importantly, Dex mitigated this process, which may indicate its application in protecting motor neurons from neurotoxic effects. This study provides evidence for the protective effect of Dex on Des‐induced motor neuron death 10 In a pediatric study, Dex reduced the incidence of sudden irritation, postoperative nausea and vomiting, postoperative pain, and Oculocardiac reflex in patients who had undergone pediatric strabismus surgery. 11 Compared with the use of propofol + Des and Des + Dex, we found that the postoperative extubation time of Dex was significantly shortened, indicating that the use of Dex + Des can achieve rapid extubation.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Interestingly, Des was found to have neurotoxic effects on motor neurons, and more importantly, Dex mitigated this process, which may indicate its application in protecting motor neurons from neurotoxic effects. This study provides evidence for the protective effect of Dex on Des‐induced motor neuron death 10 In a pediatric study, Dex reduced the incidence of sudden irritation, postoperative nausea and vomiting, postoperative pain, and Oculocardiac reflex in patients who had undergone pediatric strabismus surgery. 11 Compared with the use of propofol + Des and Des + Dex, we found that the postoperative extubation time of Dex was significantly shortened, indicating that the use of Dex + Des can achieve rapid extubation.…”
Section: Introductionmentioning
confidence: 68%
“…A meta‐analysis in 2021 of 15 randomized control study, contains a total of 2183 patients, including 1079 cases of patients who used the Dex, 1104 cases did not receive Dex, the results showed whether the inhalation anesthesia or systemic intravenous anesthesia in adult patients undergoing heart surgery, Dex administration reduced the likelihood of postoperative cognitive and behavioral dysfunction by at least 43% 24 . Des has been found to affect Moto neuron viability and maturation in vitro, but the α2‐adrenergic receptor agonist Dex attenuates the effects of Des on motor neurons, and this process is mediated by nuclear factor‐κB (NF‐κB) signaling 10 . In pediatric patients undergoing tonsillectomy or adenoidectomy, maintenance of anesthesia with Des and Dex can effectively prevent emergence agitation 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are accumulating that propofol is a contributor to neurotoxicity and neuron damage to the developing nervous system, raising widespread concern about the usage and safety of propofol in anesthesia, particularly in pediatrics [25,26]. On the other side, dexmedetomidine, an adjuvant drug widely utilized in anesthesia, antagonizes neurotoxicity posed by anesthetic drugs by modulating neuronal viability, maturation, and death [27]. The present study expounded on the neuroprotective function of dexmedetomidine on propofol-induced pyroptosis of hippocampal neurons through cooperation with the HOXA5/NLRP3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Dex regulates the NF‐κB pathway to protect against desflurane‐triggered motor neuron death. [ 9 ] Besides this, Dex attenuates lidocaine‐mediated neurotoxicity through SIRT1 suppression‐mediated FOXO3a activation. [ 10 ] In addition, the protective effects of Dex on Sev‐induced neurotoxicity were also confirmed in different studies.…”
Section: Introductionmentioning
confidence: 99%